FLIPPED LEARNING METHOD TO IMPROVE RESULTS OF LEARNING IPS CLASS VII AT SMPN 01 SETU KABUPATEN BEKASI - Sitiam Ratnasari; Dermawan Dermawan (Universitas Panca Sakti Bekasi, 2022)
The objectives to be achieved in this study are: (1) To find out whether the application of the Flipped Learning learning model can increase student learning activity in Social Studies subject class VII semester 1 SMPN 01 Setu Bekasi Regency Academic Year 2022 /2022. (2) To find out whether the Flipped Learning Model can improve the learning outcomes of Class VII SMP students in social studies subjects. This research is expected to be useful: (1) For teachers as input on the use of the Flipped Learning Learning Model in social studies learning to improve student learning outcomes, (2) for students it is expected to improve learning outcomes in social studies subjects. The results showed that the application of the Flipped Learning learning model was able to increase student activity from the pre-cycle learning activity percentage of 31%, increasing in cycle 1 to 75%, and in cycle 2 to 94%. That the Flipped Learning learning model is able to improve student learning outcomes from an average of 72.50 in the pre-cycle to an average of 75.63 in cycle 1 and 80.63 in cycle 2. In the end, the researcher hopes that the results of this Learning action research can be used by students. teachers as an alternative in learning to increase student interest and learning outcomes in social studies in particular, and all subjects in general.